Acute melatonin administration improves exercise tolerance and the metabolic recovery after exhaustive effort - Vinícius Silva Faria (Nature Portfolio, 2021)
Abstract The present study investigated the effects of acute melatonin administration on the biomarkers of energy substrates, GLUT4, and FAT/CD36 of skeletal muscle and its performance in rats subjected to exhaustive swimming exercise at an intensity corresponding to the maximal aerobic capacity (tlim). The incremental test was performed to individually determine the exercise intensity prescription and 48 h after, the animals received melatonin (10 mg·kg−1) or vehicles 30 min prior to tlim. Afterwards, the animals were euthanized 1 or 3 h after the exhaustion for blood and muscles storage. The experiment 1 found that melatonin increased the content of glycogen and GLUT4 in skeletal muscles of the animals that were euthanized 1 (p < 0.05; 22.33% and 41.87%) and 3 h (p < 0.05; 37.62% and 57.87%) after the last procedures. In experiment 2, melatonin enhanced the tlim (p = 0.01; 49.42%), the glycogen content (p < 0.05; 40.03%), GLUT4 and FAT/CD36 in exercised skeletal muscles (F = 26.83 and F = 25.28, p < 0.01). In summary, melatonin increased energy substrate availability prior to exercise, improved the exercise tolerance, and accelerated the recovery of muscle energy substrates after the tlim, possibly through GLUT4 and FAT/CD36.